(untitled) (Anclajes, 2026)
The presence of Ricardo Zelarayán in the thought and work of Fabián Casas reveals a persistent trace. This interview seeks to examine that presence within Argentine poetry in order to reflect on how a literary tradition is articulated and reconfigured through its dialogue with Zelarayán. Particular attention is given to how other writers, with whom he developed close friendships, perceived and understood him. In this regard, Casas offers a generational perspective on the figure of the Entre Ríos-born Zelarayán, linked to the aesthetic rupture represented by the poetry of the 1990s.